Ecological niche modeling and distribution of Ornithodoros hermsi associated with tick-borne relapsing fever in western North America. - Kylie M Sage; Tammi L Johnson; Michael B Teglas; Nathan C Nieto; Tom G Schwan (Public Library of Science (PLoS), 2017)
Tick-borne relapsing fever in western North America is a zoonosis caused by the spirochete bacterium, Borrelia hermsii, which is transmitted by the bite of infected Ornithodoros hermsi ticks. The pathogen is maintained in natural cycles involving small rodent hosts such as chipmunks and tree squirrels, as well as the tick vector. In order for these ticks to establish sustained and viable populations, a narrow set of environmental parameters must exist, primarily moderate temperatures and moderate to high amounts of precipitation. Maximum Entropy Species Distribution Modeling (Maxent) was used to predict the species distribution of O. hermsi and B. hermsii through time and space based on current climatic trends and future projected climate changes. From this modeling process, we found that the projected current distributions of both the tick and spirochete align with known endemic foci for the disease. Further, global climate models predict a shift in the distribution of suitable habitat for the tick vector to higher elevations. Our predictions are useful for targeting surveillance efforts in areas of high risk in western North America, increasing the efficiency and accuracy of public health investigations and vector control efforts.